If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x-26)(7x+24)=180
We move all terms to the left:
(7x-26)(7x+24)-(180)=0
We multiply parentheses ..
(+49x^2+168x-182x-624)-180=0
We get rid of parentheses
49x^2+168x-182x-624-180=0
We add all the numbers together, and all the variables
49x^2-14x-804=0
a = 49; b = -14; c = -804;
Δ = b2-4ac
Δ = -142-4·49·(-804)
Δ = 157780
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{157780}=\sqrt{196*805}=\sqrt{196}*\sqrt{805}=14\sqrt{805}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-14\sqrt{805}}{2*49}=\frac{14-14\sqrt{805}}{98} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+14\sqrt{805}}{2*49}=\frac{14+14\sqrt{805}}{98} $
| 23x-32+16=7 | | 5n-59+8n=-21 | | -5(b+8)-6=-81 | | -5w-5=20 | | 6–3y=3 | | 2x5x=90 | | 3b+2=11. | | 34=-3+9x+16+x | | 23x-32+16=70 | | 7x+3=2x18 | | -8=-3+f | | 6.908-g/g=0.173 | | 6r-70+3=-11 | | (3x+1)=(2x+10) | | 9x-1/3=6 | | 5(1+4x)=45 | | 3(x+5)^2-54=0 | | 24=6-z | | d+4=2(9-d) | | -18+3m=-(4m+4) | | 6x-70=325 | | 4(x-5)-6=2(8-x)-x | | 5/1/2=3b | | 4+y/5=8 | | 21/(x+7)=7/5 | | 5x-6=23x+8 | | .14(14r+28)=2(r+2 | | 6(-3x+-8)=-41x+23x+-2+1 | | 8/3/r-9/4r=-5/12 | | 4+10x=3x-6 | | 2x+1.5(4x-8)=32 | | 5x-11=-4(x-4) |